2012
DOI: 10.3766/jaaa.23.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss and Delayed Complete Sudden Spontaneous Recovery

Abstract: This is a case report of a 53-yr-old female who experienced sudden sensorineural hearing loss (SSNHL) accompanied by roaring tinnitus in her right ear. The patient's hearing partially improved in the low frequencies in response to intratympanic injections. Given that her hearing loss did not improve further, the patient was fitted with a hearing aid to mask the tinnitus and restore a sense of balance between the two ears. Approximately 9 mo postonset of the SSNHL, a complete spontaneous recovery of hearing occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
3
0
2
Order By: Relevance
“…Similarly to the case report that a complete recovery of hearing delaying approximately 9 month postonset of the SSNHL [12], this current outcomes of delayed recovery in hearing may indicate the pathological cause for the IS-SNHL involved a process that was capable of repair or regeneration, thus ruling out pathologies related to cochlear hair cell destruction or nerve fiber loss. There are a number of obvious hearing loss treatment questions that remain unanswered.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly to the case report that a complete recovery of hearing delaying approximately 9 month postonset of the SSNHL [12], this current outcomes of delayed recovery in hearing may indicate the pathological cause for the IS-SNHL involved a process that was capable of repair or regeneration, thus ruling out pathologies related to cochlear hair cell destruction or nerve fiber loss. There are a number of obvious hearing loss treatment questions that remain unanswered.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, after a 10-day course of systemic steroid therapy and a long-term follow-up of more than 3 months, Yeo et al 41 found that 35.54%, 8.26%, and 1.65% of patients with SSNHL recovered within 1 month, 1-3 months, and >3 months, respectively, while a previous case report described a complete spontaneous recovery of hearing at approximately 9 months after the onset of SSNHL. 42 Plontke et al 43 found that hearing gain and final hearing thresholds appeared to be independent of the start of secondary therapy. Therefore, further studies are needed to determine of the duration of time after which the initiation of treatment for SSNHL is ineffective.…”
Section: Duration Of Steroid Therapymentioning
confidence: 98%
“…41 found that 35.54%, 8.26%, and 1.65% of patients with SSNHL recovered within 1 month, 1–3 months, and >3 months, respectively, while a previous case report described a complete spontaneous recovery of hearing at approximately 9 months after the onset of SSNHL. 42 Plontke et al. 43 found that hearing gain and final hearing thresholds appeared to be independent of the start of secondary therapy.…”
Section: Duration Of Steroid Therapymentioning
confidence: 99%
“…Hearing recovery according to pre-ITD PTA 력검사 시점이 증상 발현 직후가 아닌 환자가 병원에 내원한 시점이었다는 것과, 타 병원에서 이미 경구 스테로이드 치료를 받은 후 내원했을 경우 증상 발생 당시의 청력검사 결과가 첨 부되지 않았다는 제한점이 있다. 또한 돌발성 난청은 자연회 복의 가능성이 있으며 일부는 경구 스테로이드 등의 전신적 치 료에 지연성 회복을 보이는 경향도 있어 이에 대한 고려가 필요할 것으로 보인다 14). …”
unclassified